توثيق التراث الأنثروبولوجي والتواصل مع التجربة الفولكلورية - جاد, مصطفى (Changement Social, 2018)
Documentation of the Arabanthropologicalheritagewillcontribute to the advancement of scientificresearch in bothfields (folklore and anthropology), especially in the context of the definition of Arab efforts that are still operating in isolatedislands, as are the folkloric efforts that are still in need of reunification. This requires close cooperationbetweenArabscientists in bothfields, regardless of their respective tools and approaches.